The development of empowerment model on academic administration in small-size basic education schools / Kasama Somsriphaeng, Surithong Srisa-ard, and Tirawat Yeamsang - Somsriphaeng, Kasama; Srisa-ard, Surithong; Yeamsang, Tirawat (Universiti Teknologi MARA, Perlis, 2011)
The purposes of this research were: 1) to examine and investigate the state of Empowerment activities on Academic Administration in Small-size Basic Education Schools, and 2) to develop model of Empowerment on Academic Administration in Small-size Basic Education Schools. The study was divided into three phases. Phase I was related to the examination and investigating the state of Empowerment activities on Academic Administration in Small-size Basic Education Schools. The samples were 106 school administrators under the Office of Sakon Nakhon Primary Educational Service Area 2 in academic year 2009. The statistics used in analyzing data were: frequency, percentage, mean and standard deviation. The interview of the experts and the in-depth case study of 1 small sized primary school. In phase II, the structured interview of 9 experts in small-size schools’ administration on the empowerment model on Academic Administration of small-size schools were conducted. The parallel seminar of the selected 32 small-size school administrators on the development of the model was also conducted. The study found that the school principal and teachers felt that they were empowered namely giving supporting, giving opportunity, participating decision, leadership building, teamwork building, and motivation. The academic activities carried out by the small-size school included 1) using mass media innovation development, 2) system guaranteeing quality within school development, 3) learning resource development, 4) research and quality of education development, 5) education supervision development, 6) guidance and counseling of education development, 7) learning process development, 8) schools’ curriculum development, and 9) measurement and evaluation development. After the experiment, the result showed that the mean postworkshop score was higher than the pre-workshop all aspect with the means value at 4.99 rating scale evaluation.